2022
DOI: 10.3390/bs12110443
|View full text |Cite
|
Sign up to set email alerts
|

Self-Leadership and Innovative Behavior: Mediation of Informal Learning and Moderation of Social Capital

Abstract: As the business environment is rapidly changing, interest in the innovation of organizational members is accelerating. Therefore, this study investigated how individual-level resources, particularly self-leadership, affect workers’ innovative behavior. Many studies have emphasized that employee initiative can lead to job performance at the individual level and organizational performance improvement. Self-leadership is a spontaneous and an active behavior, or mindset, defined as the ability to lead an individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Lastly, we used the PROCESS macro in SPSS 25 to analyze Hypothesis 4 [ 103 ]; Table 7 and Table 8 . For innovative behavior as a dependent variable, according to the findings from 5000 resamples, the indirect effect of transformational leadership on innovative behavior was statistically significant at high levels of moderation (conditional indirect effect = 0.19, SE = 0.03, 95% CI = 0.14 to 0.25) but weakened at low levels (conditional indirect effect = 0.12, SE = 0.03, 95% CI = 0.07 to 0.18).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we used the PROCESS macro in SPSS 25 to analyze Hypothesis 4 [ 103 ]; Table 7 and Table 8 . For innovative behavior as a dependent variable, according to the findings from 5000 resamples, the indirect effect of transformational leadership on innovative behavior was statistically significant at high levels of moderation (conditional indirect effect = 0.19, SE = 0.03, 95% CI = 0.14 to 0.25) but weakened at low levels (conditional indirect effect = 0.12, SE = 0.03, 95% CI = 0.07 to 0.18).…”
Section: Resultsmentioning
confidence: 99%
“…The study by Hyesun Kang and colleagues shows that people with higher educational qualifications generally have higher levels of self-leadership ( 28 ); however, when considering the impact of self-leadership on quality of life, the difference is not significant. This indicates that self-leadership actions for managing and promoting personal health are not affected by educational level.…”
Section: Discussionmentioning
confidence: 99%
“…Learning increased the accumulation of knowledge and experience that are supported to create a new idea (Kang et al, 2022). Previous study has found this to be a prerequisite for innovation is resource availability or the ability to acquire resources through learning (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 98%